Chimeric Yellow Fever/Dengue Virus as a Candidate Dengue Vaccine: Quantitation of the Dengue Virus-Specific CD8 T-Cell Response - van der Most, Robbert G. (American Society for Microbiology, 2000)
We have constructed a chimeric yellow fever/dengue (YF/DEN) virus, which expresses the premembrane (prM) and envelope (E) genes from DEN type 2 (DEN-2) virus in a YF virus (YFV-17D) genetic background. Immunization of BALB/c mice with this chimeric virus induced a CD8 T-cell response specific for the DEN-2 virus prM and E proteins. This response protected YF/DEN virus-immunized mice against lethal dengue encephalitis. Control mice immunized with the parental YFV-17D were not protected against DEN-2 virus challenge, indicating that protection was mediated by the DEN-2 virus prM- and E-specific immune responses. YF/DEN vaccine-primed CD8 T cells expanded and were efficiently recruited into the central nervous systems of DEN-2 virus challenged mice. At 5 days after challenge, 3 to 4% of CD8 T cells in the spleen were specific for the prM and E proteins, and 34% of CD8 T cells in the central nervous system recognized these proteins. Depletion of either CD4 or CD8 T cells, or both, strongly reduced the protective efficacy of the YF/DEN virus, stressing the key role of the antiviral T-cell response.